2010
DOI: 10.1128/ec.00112-10
|View full text |Cite
|
Sign up to set email alerts
|

The N Terminus of Phosphodiesterase TbrPDEB1 of Trypanosoma brucei Contains the Signal for Integration into the Flagellar Skeleton

Abstract: The precise subcellular localization of the components of the cyclic AMP (cAMP) signaling pathways is a crucial aspect of eukaryotic intracellular signaling. In the human pathogen Trypanosoma brucei, the strict control of cAMP levels by cAMP-specific phosphodiesterases is essential for parasite survival, both in cell culture and in the infected host. Among the five cyclic nucleotide phosphodiesterases identified in this organism, two closely related isoenzymes, T. brucei PDEB1 (TbrPDEB1) (PDEB1) and TbrPDEB2 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 56 publications
1
13
0
Order By: Relevance
“…This observation is not surprising, since most of these proteins are from mammals that are highly divergent from ancient parasitic protozoa. In addition, this sequence is not related to those involved in flagellar localization of non-membrane proteins that have been identified among the kinetoplastid protozoa (Luginbuehl et al, 2010;Pullen et al, 2004), and this result would be consistent with the notion that flagellar membrane proteins traffic to that organelle by a different mechanism than non-membrane proteins. Furthermore, the NPM motif is not obviously represented within the sequence of two other membrane proteins that traffic to the flagellum in Leishmania species, the polytopic aquaporin 1 from L. major (Figarella et al, 2007) and SMP-1, a dually acylated peripheral membrane protein from Leishmania (Tull et al, 2004).…”
Section: Overviewsupporting
confidence: 76%
“…This observation is not surprising, since most of these proteins are from mammals that are highly divergent from ancient parasitic protozoa. In addition, this sequence is not related to those involved in flagellar localization of non-membrane proteins that have been identified among the kinetoplastid protozoa (Luginbuehl et al, 2010;Pullen et al, 2004), and this result would be consistent with the notion that flagellar membrane proteins traffic to that organelle by a different mechanism than non-membrane proteins. Furthermore, the NPM motif is not obviously represented within the sequence of two other membrane proteins that traffic to the flagellum in Leishmania species, the polytopic aquaporin 1 from L. major (Figarella et al, 2007) and SMP-1, a dually acylated peripheral membrane protein from Leishmania (Tull et al, 2004).…”
Section: Overviewsupporting
confidence: 76%
“…PDEB1 and PDEB2 are two tandemly arranged genes that code for two highly similar, cAMP-specific PDEs. Despite their high similarity, their subcellular localization is quite distinct, with TbrPDEB1 localized predominantly in the flagellum, whereas TbrPDEB2 is mainly located within the cell body [64-68]. PDEC codes for a dual-substrate PDE that contains a FYVE domain at its N -terminus [69,70].…”
Section: The Pdes Of T Brucei and L Majormentioning
confidence: 99%
“…From these, only TcrPDEC has been validated as a therapeutic target [76]. The enzyme has been described by Kunz et al as an unusual dual-substrate PDE [64]. It is able to hydrolyze cAMP as well as cGMP, although the biological significance of the latter activity is unclear.…”
Section: The Pdes Of T Brucei and L Majormentioning
confidence: 99%
“…Two alleles for TbrPDEB2 were identified in the strain used in the protein localization studies, but allelic variation was found not to be responsible for the dual localization (Kunz et al ., 2009). Instead, the N‐terminal 70 amino acids of the two proteins appear to contain the signal for localization, with that from PDEB1 being sufficient to result in specific transport of a green fluorescent protein (GFP) fusion protein to the PFR, whereas the same section from PDEB2 yielded localization mainly in the cell body (Luginbuehl et al ., 2010). Mutating a specific leucine residue to cysteine, and vice versa, resulted in a switching of the localization of the GFP fusion proteins.…”
Section: Pdebmentioning
confidence: 99%